Investigation of cubic GaN quantum dots grown by the Stranski‐Krastanov process. Issue 4 (12th February 2015) - Bürger, M.; Lindner, J. K. N.; Reuter, D.; As, D. J.
Abstract: We investigate the formation of cubic GaN quantum dots (QDs) on pseudomorphic strained cubic AlN layers on 3C‐SiC (001) substrates grown by means of molecular beam epitaxy. Surface morphologies of various QD sizes and densities were obtained from uncapped samples by atomic force microscopy. These results were correlated with similar but capped samples by photoluminescence experiments. The QD density varies by one order of magnitude from ∼1x10 10 cm ‐2 to ∼1x10 11 cm ‐2 as a function of the GaN coverage on the surface. The initial layer thickness for the creation of cubic GaN QDs on cubic AlN was obtained to 1.95 monolayers by a comparison between the experimental results and an analytical model. Our results reveal the strain‐driven Stranski‐Krastanov growth mode as the main formation process of the cubic GaN QDs. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)